Maternal obesity support services: a qualitative study of the perspectives of women and midwives - Dearden Andy M; Garland Carolyn; Arden Madelynne A; McSeveny Kerry; Furness Penny J; Soltani Hora (BMC, 2011)
Abstract Background Twenty percent of pregnant women in the UK are obese (BMI ≥ 30 kg/m2), reflecting the growing public health challenge of obesity in the 21st century. Obesity increases the risk of adverse outcomes during pregnancy and birth and has significant cost implications for maternity services. Gestational weight management strategies are a high priority; however the evidence for effective, feasible and acceptable weight control interventions is limited and inconclusive. This qualitative study explored the experiences and perceptions of pregnant women and midwives regarding existing support for weight management in pregnancy and their ideas for service development. Methods A purposive sample of 6 women and 7 midwives from Doncaster, UK, participated in two separate focus groups. Transcripts were analysed thematically. Results Two overarching themes were identified, 'Explanations for obesity and weight management' and 'Best care for pregnant women'. 'Explanations' included a lack of knowledge about weight, diet and exercise during pregnancy; self-talk messages which excused overeating; difficulties maintaining motivation for a healthy lifestyle; the importance of social support; stigmatisation; and sensitivity surrounding communication about obesity between midwives and their clients. 'Best care' suggested that weight management required care which was consistent and continuous, supportive and non-judgemental, and which created opportunities for interaction and mutual support between obese pregnant women. Conclusions Women need unambiguous advice regarding healthy lifestyles, diet and exercise in pregnancy to address a lack of knowledge and a tendency towards unhelpful self-talk messages. Midwives expressed difficulties in communicating with their clients about their weight, given awareness that obesity is a sensitive and potentially stigmatising issue. This indicates more could be done to educate and support them in their work with obese pregnant women. Motivation and social support were strong explanatory themes for obesity and weight management, suggesting that interventions should focus on motivational strategies and social support facilitation.